Generation of neutralizing aptamers against herpes simplex virus type 2: potential components of multivalent microbicides. - Moore, M; Bunka, D; Forzan, M; Spear, P; Stockley, P; McGowan, I; James, W (2011)
The prophylactic use of topical antiviral agents has recently been validated by the reduction in human immunodeficiency virus (HIV) type 1 infection incidence seen using tonofovir-containing microbicides. In order to develop a wide-spectrum microbicide to prevent infection with a wide range of sexually transmitted viruses, we have previously reported the development of HIV-neutralizing aptamers and here report the isolation and characterization of aptamers that neutralize herpes simplex virus type 2 (HSV-2). These aptamers bind the envelope glycoprotein (gD), are potent (IC(50) of 20-50 nM) and are able to block infection pathways dependent on both major entry receptors, Nectin1 and HVEM. Structural analysis and mutagenesis of these aptamers reveal a core specificity element that could provide the basis for pharmaceutical development. As HSV-2 is a major risk factor for the acquisition of HIV-1, a microbicide capable of preventing HSV-2 infection would not only reduce the morbidity associated with HSV-2, but also that derived from HIV-1.